INFLUENCE OF LEADERSHIP AND EMPLOYEE COMMITMENT TO JOB PERFORMANCE OF MOTIVATION AS AN INTERVENING VARIABLE IMMIGRATION OFFICE CLASS 1IN SOUTH JAKARTA - Agustinus Apono, Abdul Rivai & Suharto (International Journal of Research Science and Management, 2018)
This study aims to determine the effect of leadership and employee commitment to performance excellence through the motivation of employees at the Office of Immigration Class 1 South Jakarta. The study used a sample of 61 employees with sampling random sampling techniques and analysis of research using path analysis. The results showed that there was influence employee commitment to the job performance through motivation is 0.994 x 0.699 = 0.695. While the influence of employee commitment to the job performance is 0.722. In this case it is known that directly influence employees' commitment to greater job performance when compared to the indirect influence through motivation, namely 0.722 > 0.695, so it can be said that the motivation not as an intervening variable.